Pengaruh Capital Adequacyratio dan Nonperforming Loan Melalui Kebijakan Perkreditan Terhadap Laba Bersih Pada Bank Pembangunan Daerah di Indonesia Periode 2015 - 2019 - Ira Febrianti; Rani Dewi Lestari (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
This Research study aims to analyze the effect of the capital adequacy ratio and non-performing loans through credit policy on net income in BPD banking in Indonesia. Research Methodology use the data panel regression analysis method with the model used is fixed effect. The results of this study show that the capital adequacy ratio (Xj), non-performing loans (X2) directly and indirectly have a negative effect on net income (Z). And it is known that there is a partial non-performing loan (X2) effect on the loan to deposit ratio(Y).